USE OF MODERN MATERIALS FOR CAMOUFLAGE OF MILITARY EQUIPMENT AND PERSONAL EQUIPMENT - Vasylenko, Viktoriia; Kukosh, Yuliia; Ziemtsova, Polina (Theory and practice of design, 2023)
The article provides an analysis of modern materials for comprehensive protection of personnel, military equipment and objects from enemy attacks. The purpose of this work is to analyze the use of modern materials in the development and implementation of means of camouflage for military equipment and personal equipment. The methodology of the article consists in the collection and analysis of existing materials that exist for camouflage, classification of technical means, modeling of camouflage means for objects of military equipment and special clothing. The results of the article are the disclosure of the essence and content of the complex use of materials of industrial production, which are intended for arranging the masking of people and objects from detection by various means. The results of the study can be useful for military science specialists, designers and manufacturers of military equipment, as well as for military strategists and operational planners. The practical significance of the material of the article lies in the fact that it reveals the basic principles of using industrially produced materials in masking measures. This analysis explores a range of innovative materials, including adaptive textiles, infrared reflective coatings and nanotechnology-based solutions, and their applications in camouflage design for military vehicles such as tanks, aircraft and infantry vehicles. This article considers the use of modern materials for camouflage of military equipment and personnel. The author examines current technologies and materials used to increase the effectiveness of hiding military equipment and personnel on the battlefield. The article considers not only traditional camouflage means, but also innovative materials, such as thermosensitive polymers, nanotechnology, and others, which allow effective camouflage of military equipment in various conditions. The advantages and disadvantages of using such materials are highlighted, as well as their possible prospects in the aspect of improving means of concealment on the battlefield. The scientific novelty of the article lies in the study of the integration of these materials into personal equipment, such as uniforms, body armor and accessories, which increases the effectiveness of individual soldiers on the battlefield. The scientific novelty of the article lies in its comprehensive approach to the design of camouflage items, recommendations for the selection of materials that meet the practical needs of the military. We present models made of materials that contribute to the camouflage of military equipment and the military themselves. The types of camouflage materials and the possibility of their practical use, the latest achievements in materials science and their influence on military camouflage are investigated.